2013
DOI: 10.1371/journal.pone.0055235
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Error Related Neuronal Responses Recorded by Electrocorticography in Humans during Continuous Movements

Abstract: BackgroundBrain-machine interfaces (BMIs) can translate the neuronal activity underlying a user’s movement intention into movements of an artificial effector. In spite of continuous improvements, errors in movement decoding are still a major problem of current BMI systems. If the difference between the decoded and intended movements becomes noticeable, it may lead to an execution error. Outcome errors, where subjects fail to reach a certain movement goal, are also present during online BMI operation. Detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 82 publications
2
59
0
Order By: Relevance
“…Thus, the key scientific contribution of this study is that, to our knowledge, this is the first report of task outcome-related spiking neural activity in M1 and PMd. These results using intracortical recordings significantly expand a recent ECoG study [19,71] which suggested the presence of error signals in motor cortex. First, we showed that error signals are present in both PMd and M1, and that they appear earlier in PMd compared to M1.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the key scientific contribution of this study is that, to our knowledge, this is the first report of task outcome-related spiking neural activity in M1 and PMd. These results using intracortical recordings significantly expand a recent ECoG study [19,71] which suggested the presence of error signals in motor cortex. First, we showed that error signals are present in both PMd and M1, and that they appear earlier in PMd compared to M1.…”
Section: Discussionsupporting
confidence: 83%
“…This open question is an important area for future investigation; recent encouraging ECoG results indeed showed evidence for such activity in motor cortex [71]. We predict that one source of differences that may be encountered during translation stems from human BMI movements being self-initiated by the user, in contrast to experimenter-paced monkey tasks.…”
Section: Discussionmentioning
confidence: 91%
“…ACC takes part in action monitoring and detection of errors [26]. On the other hand in line with our results, non-haptic Electrocorticography (ECoG) invasive studies on execution errors during continuous 1D motion [6,7], did not show significant error related activation in the ACC. Using fMRI, random target jumps and visuo-motor rotations were found to activate the posterior or anterior aspects of the parietal cortex, respectively; but not the ACC [33].…”
Section: Discussionsupporting
confidence: 88%
“…Interface errors can occur in any type of controlled motion, and are defined as execution errors. Execution errors occur when an unexpected movement was performed instead of the intended one [6][7][8]. Error Related Potentials (ErrPs) evoked by errors and embedded in the ongoing Electroencephalography (EEG) (non-invasive brain signal recording) [8] are used to decrease the misclassification rate [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation